Frequency of Polycythemia in Patients with Stroke - Kamran Ahmad, Hafiz Rahman, Junaid Raqib, Sultana Shaheen, Mohammad Imran Younus (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Stroke is a neurological deficit of vascular origin that persists for more than 24 hours, affecting approximately 16.9 million people annually. Among the various contributors to stroke, one is polycythaemia, characterized by an increase in red blood cell mass, often measured through hematocrit levels. Building on this, the present study aims to determine the frequency of polycythemia in patients with stroke, addressing the limited data available on the subjec.t. Objectives: Investigate the prevalence of polycythemia in stroke patients and explore its relationship with demographic and clinical factors. Methods: A cross-sectional, descriptive study was conducted at the Department of General Medicine, Hayatabad Medical Complex, Peshawar, from December 2020 to May 2021. To determine an appropriate sample size, 121 patients were calculated using the WHO sample size calculator. To minimize bias, strict inclusion and exclusion criteria were applied. Data were then collected from stroke patients, including blood samples for a full blood count and haematocrit level analysis. Subsequently, results were recorded in a pre-prepared proforma and analysed using IBM SPSS. Results: Patients studied, 83.5% were male, with a mean age of 43.48 ± 9.84 years. 60.3% had ischemic stroke, and 53.7% had diabetes, 66.1% were hypertensive, and 56.2% had chronic kidney disease (CKD). The prevalence of polycythaemia was 62.0%. Further analysis revealed that polycythaemia was significantly associated with stroke type, diabetes, hypertension, CKD, and haematocrit levels (p<0.05), but non-significantly associated with age and gender (p>0.05). Conclusion: polycythemia is prevalent among stroke patients and is significantly linked to factors like diabetes, CKD, and hypertension. These findings suggest it is crucial to consider polycythaemia and other myeloproliferative disorders in the evaluation and management of stroke patients, ensuring that these conditions are addressed to improve patient outcomes. Keywords: Stroke, Polycythaemia, Haematocrit level, Diabetes, Hypertension, Chronic Kidney Disease